An Overview of Post-structuralism in Comparative Analysis of Pakistan and Türkiye in Managing Refugee Crisis - Khushboo Fatima; Dr. Amna Mahmood; Muneeba Shahid (Journal of Research in Social Sciences, 2022)
Pakistan and Türkiye host millions of registered Afghan and Syrian refugee respectively and provide them with humanitarian aid. This study highlights the picture demonstrated to the world, made by Türkiye and Pakistan to address refugee crises. In Middle Eastern region, Türkiye is now rising as new major power for the Muslim countries in the multifaceted context, including sympathetically letting in Syrian refugees; however, the in-depth truth is entirely dissimilar. Religious and autonomist fulfilment are fundamental components in Türkiye discrepancy of its dignity in facilitating Syrian refugees with empathy and assistance. Being a strong economy compared to Pakistan and an active member of the international community, Türkiye is violating international law on various refugees' accommodation. Interestingly, in spite of inconsequential assets and lesser affirmation from the global community, Pakistan's extraordinary responsibility as a prototypical host for forty years of emigrants from Afghanistan. Furthermore, the covid-19 pandemic circumstances also pose formidable challenges to both states and develop different refugees' policies. Once again, with an on-going overabundance of challenges, Pakistan provides maximum accommodation to Afghan refugees to survive the pandemic era compared to Türkiye. The research is mainly focused on how Türkiye and Pakistan has managed their socioeconomic resources in handling the refugee crisis.